ANALISIS KESULITAN MEMBACA SISWA KELAS I SD BERDASARKAN PERSPEKTIF TEORI EKOLOGI BROFENBRENNER - Nugraha Nasution; Sylvia Ramadhani; May Adelia; Elly Prihasti Wuriyani; Khairil Anshari (JURNAL ILMIAH NUSANTARA, 2025)
Reading difficulties in first grade elementary school students are a challenge in the learning process, especially in understanding letters, syllables, and words. This study aims to analyze students' reading difficulties based on the perspective of Bronfenbrenner's ecological theory, which highlights the influence of the environment on individual development. This study uses a qualitative approach with a case study method conducted at UPT SD Negeri 060925 Medan. Data were collected through observation, reading tests, and interviews with four students who had reading difficulties. The results of the study indicate that environmental factors play a significant role in influencing students' reading abilities. The microsystem environment (family and school) influences literacy development through interactions with parents and teachers. Coordination between the home and school environments in the mesosystem also has an impact on the consistency of reading practices. In addition, the ecosystem and macrosystem, including reading culture in society and social expectations, play a role in shaping students' motivation. Chronosystem factors, such as curriculum changes and events in students' lives, also influence their reading development. The conclusion of this study emphasizes the importance of a holistic approach in dealing with first grade students' reading difficulties, by involving support from family, school, and community. Bronfenbrenner's ecological theory-based intervention can be an effective strategy in improving students' reading skills from an early age.